Quelles sont les conditions historiques de la fabrique de la mémoire ? - Stéphane Michonneau (Cahiers de Civilisation Espagnole Contemporaine)
The study of the memory of the Spanish Civil War and subsequent repression under Franco’s dictatorship must distinguish between memorialization and the scientific discipline of history. The expression «recovery of historical memory», so common nowadays in Spain, tends to blur this distinction. Consequently, the logic of memorialization requires an interrogation of the historical conditions of the production of memorial narrative, which bridges two conceptions of memory that are difficult to reconcile. As such, the status of the author –as witness or investigator– must be taken into account. A draft chronology of the history of memory in Spain offers the opportunity to better situate authors in relation to the context of production. In this sense the logics of activism from the years 2000 onward are of particular interest, a period in which memorial production emerged and in which Spain entered an era of hypermnesia.